PERKEMBANGAN USAHA UMKM SEBELUM DAN SESUDAH MENERIMA PEMBIAYAAN MURABAHAH PADA BMT BEN SEJAHTERA KECAMATAN KROYA KABUPATEN CILACAP - Reni Wiyarti; Heru Cahyo; Nirmala Nirmala (FEB UNWIKU PURWOKERTO, 2020)
The purpose of this study was to determine the development of micro, small and medium enterprises before and after receiving murabahah financing at BMT Ben Sejahtera Kroya. This research is quantitative research and the method is purposive sampling method. The population in this study were all members of the Murabahah Financing of BMT Ben Sejahtera Kroya is 150 members in 2017. The analysis technique in this study was the Wilcoxon Signed Rank test. Whereas, the data processing used the SPSS for Windows Release 22 program.The results of the research on sales turnover before and after receiving Murabahah financing are (Asymp.Sig. (2-tailed) of 0,000 where the value is less than the research critical limit of 0.05, income of -9.101 with ( Asymp. Sig. (2-tailed) of 0,000 where the value is less than the research critical limit of 0.05, profit equal to -8,791 with (Asymp. Sig. (2-tailed) of 0,000 where the value is less than the research critical limit of 0.05, meaning H1, H2 and H3 are accepted and H0 is rejected